Motivation as Realisation of Needs and Interests - Alfred Prigl; Henrieta Priglova; Bronislava Jakubikova (Communications - Scientific letters of the University of Zilina, 2007)
In the study, the authors analyse all the factors of human motivation which lead to a concrete act of a subject. It is not only about mechanical analysis of the components of motivation structure, but also about reciprocal dynamic links and connections. It deals with the relation between motives, needs and interests as a multilateral continual process.